Effets des grands angles de zénith et de la couverture nuageuse sur l’éclairement sous-marin: implications pour la production primaire dans l'océan Arctique - Ayyala Somayajula, Srikanth (Université de Laval, 2019)
The process of photosynthesis requires the energy from sunlight and takes place essentially in the euphotic layer of the oceans. In addition to other variables (i.e., chlorophyll a and photosynthetic parameters) a suitable knowledge of light field in terms of photosynthetically available radiation (PAR) at any given location, depth and time is an important input parameter required by marine ecosystem models. The work included in this thesis examines how larger solar zenith angles, different cloud conditions that are characteristic features of high latitude regions, especially in Arctic, might affect the accuracy of surface irradiance estimates. Further, main focus was on the effects of high frequency variations in the light field on primary production. Surface PAR estimated from different models were compared with high frequency in situ time series measurements of PAR a buoy located in Mediterranean Sea. It was examined how uncertainties due to larger solar zenith angles under varying cloud conditions might affect the accuracy of surface irradiance. Objective ranking method was used to identify the best methods. Methods tested under low sun elevations exhibited uncertainties as large as 50% under all sky conditions. Model performances were dependent on cloud properties and products. Accuracy of a semianalytical model for coefficient of vertical diffuse attenuation of surface irradiance (!"#) based on optical properties inherent to the water itself (absorption and scattering), and solar zenith angle was examined under larger solar zenith angels and cloud conditions. Extensive radiative transfer simulations were performed to quantify the uncertainties due to large solar zenith angles and clouds on the estimates of diffuse attenuation coefficient. The uncertainties under both these conditions are due to the variability in the proportions of direct and diffuse parts of the total irradiance reaching the surface and in the water column. Also, an improved model parameterization proposed to estimate !"# under large ...